Trends in employment of graduates of ecology education in higher education - Adizov Bakhtiyor; Tokhirov Javlon; Hamidov Saidjon (E3S Web of Conferences)
The changes taking place in the socio-economic policy of the countries of the world lead to serious changes in the higher education system at the global level. The experience of countries such as Japan, Finland, South Korea, Germany, the USA, the PRC, and the United Kingdom, which have a higher education system with high potential, shows that the level of economic growth of these countries is steadily growing under the influence of the quality and competitiveness of trained specialists. shows. The article contains the opinions, conclusions and suggestions of the authors on the topic.